Gambaran Pengetahuan Ibu Tentang Kartu Menuju Sehat Balita Di Wilayah Kerja Puskesmas Sitiung Kabupaten Dharmasraya Tahun 2023 - Putri, Neneng Syah; Purwati, Rati; Yuliawati, Eny (Bunda Edu-Midwifery Journal (BEMJ), 2023)
for toddlers has been used, which is the main instrument for coaching. The health card is a series of activities consisting of regular assessment of the growth and development of toddlers which consists of weighing, filling out maternal and child health books. The aim of the research is to find out the description of mothers' knowledge of toddlers about Card Towards Health. The research design used is descriptive research. The population in this study were all mothers with toddlers totaling 749 toddlers using the Proportional Sampling sampling technique so that a sample of 42 respondents was obtained and the location of this research was in the working area of ​​the Sitiung Health Center, namely in Jorong Piruko Selatan, Piruko Utara and Posyandu Pratiwi.The results showed that of the 42 respondents, the majority had moderate knowledge, 22 respondents (52.4%) and a minority with low knowledge, 2 respondents (4.8%). It is suggested to the puskesmas to be able to always provide education about the importance of KMS for detecting the growth and development of toddlers.